Tackling that test : everything you wanted to know about taking tests and exams - Withers, Graeme. (Australian Council for Educational Research, 1999)
This book is about: Things to ask yourself before your test; Tests and examinations-what's the difference?; Feeling good about a test or an exam; Tactics and strategies before the test session; ...